The Crime Of Illegal Gain In The Light Of Iraqi Law And International Agreements - Hassan Khalid, Mohammed (Opción, 2019)
This study deals with the crime of graft as one of the most serious crimes of a private nature as it relates to the civil service and a certain category of em- ployees, exclusively by law. The researcher divided this study into two main subjects where the first section of it came under the title (What is graft), while the researcher The second of them was entitled (legal regulation of the crime of graft), and for the purpose of taking note of the subject of the research com- pletely, we have divided each research into several demands, which branch- es of several branches of the need for the research for the purpose of fully knowing the details of the research, has reached the researcher at the end of this study a The crime of graft has aroused controversy and controversy wide jurisprudence on the extent of its legitimacy and conflict with the provisions of the Constitution, as it is one of the most difficult crimes in terms of proof because of the character of the perpetrator in this crime and its wide influ- ence facilitates the concealment of the features of the crime and its effects, as the researcher recommended the need to tighten The penalty for graft crime is commensurate with the gravity of this crime, its gravity and its effects on society, and the call to benefit from the UN expertise in the field of combating corruption after Iraq acceded to the 2004 UN Convention.